ANALISIS MANAJEMEN RISIKO DALAM MENGURANGI KREDIT MACET DI BANK BTPN SYARIAH CABANG NGETOS - A’yun, Aniqurotul; Rukmini, Meme; Kristanti, Desi (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2023)
The research entitled “Analysis of Risk Management in Reducing Bad Loans at Bank BTPN Syariah” aims to analyze the risk management implemented at Bank BTPN Syariah. The method used in this research is the qualitative method. The data sources used are primary data obtained directly from field research and secondary data, namely data or knowledge obtained through library research, writing articles, journals, trusted internet sites, and other data sources. Based on the research results, the researcher can conclude that the credit risk management implemented at Bank BTPN Syariah is carried out in two stages, namely: 1) The stage of risk identification and risk management. Identification of bad credit risk starts with prospective customers submitting financing applications, due diligence through surveys and interviews that adhere to the 5C principles (Character, Capacity, Capital, Collateral, and Condition) as well as customer maintenance which is carried out correctly and periodically. 2) Management of bad credit risk begins with coaching customers by means of periodic billing and ensuring the group's active role in helping smooth installments to reduce the risk of bad loans and rescuing bad loans is carried out through a restructuring process, namely rescheduling. 3) Analysis of bad credit risk is in accordance with risk management principles. Where there are no obstacles that hinder the application of these risk management principles, evidenced by the improved condition of the branch and the start of the installment payment process using the online system. And also the smooth operation of the company's operations and new programs issued by the company.